Multidisciplinary Excellence in Medicine: A Bibliometric Analysis of Book Authorship (1991-2025) - Koley, Susanta; Thakur, Rekha (Information Research Communications, 2026)
Aim The main aim of this study is to assess medical book productivity during 1991-2025, by multitalented minds/ authors. Using bibliometric techniques, the study provides a quantitative analysis of his research output and highlights his impact on the field. Background Medical book publishing has been central to the dissemination of medical knowledge, with its growth in India accelerating during the colonial period, particularly in academic hubs such as Calcutta, which emerged as a major centre for medical education and scholarly publishing. Calcutta also gained global recognition when Sir Ronald Ross was awarded the 1902 Nobel Prize in Physiology or Medicine for discovering the mosquito transmission of malaria, a breakthrough achieved through research conducted largely in Calcutta, significantly advancing tropical medicine. The tradition of medical writing dates back to ancient texts like Egypt’s Ebers Papyrus and India’s Charaka and Sushruta Samhitas, laying the foundation for modern medical publishing. Methodology This study collected data on 3504 medical books publications from Jaypee Digital-Explore Health Science, India, databases during the period of April 12 to October 10, 2025 and other sources. Key details from each publication were carefully selected, checked, and organized using Microsoft Excel and Word. Bibliometric methods were then used to analyze the data for mapping the contributions of multitalented medical authors to medical research. Findings Medical book publishing from 1991-2025 showed substantial growth, with a total of 3,504 books published and a shift from sporadic early output (1991-2002) to a mature, stable phase after 2009, and Relative Growth Rates (ReGR) peaking at 1.30 in 2003 before gradually declining, while Doubling Time (Dt) increased up to 69 years by 2025, indicating maturation. Multi-authored works dominated at 53.59%, with a preference for small collaborative groups, particularly in interdisciplinary fields like Alternative Medicine, Obstetrics & Gynaecology, and Ophthalmology. A core group of highly productive authors, led by Narendra Malhotra (73 books), contributed disproportionately to output, while 73.35% of authors remained single-discipline, highlighting both specialization and the growing role of collaboration in medical knowledge production. It is confirming that a small number of multitalented scholars drive the majority of medical publishing under Jaypee. Finally, Lotka’s Law shows the expected inverse relationship between authors and publications, but chi-square analysis indicates significant deviations from this pattern. Conclusion All stakeholders-such as parents, teachers, multitalented authors, book publishers, knowledge converters, and various offline and online vendors-play an important role in strengthening our education system. Intellectual content, its expression and manifestation, and its transformation into usable knowledge are fundamental requirements of an effective information system. Analysing various important sources of knowledge dissemination is a key responsibility of librarians and information scientists. This study, it is hoped, will be highly beneficial to students, researchers, and teachers in supporting effective information retrieval.
Keywords: Bibliometric; Informetric; Medical books; Multitalented minds; Medical scientist; Jaypee Digital-Explore Health Science; P-P Model in education system; Doctor; Nursing professionals; India